Time Will Tell: Ambiguous Non-Responses on Internet Relay Chat - Rintel, Sean; Pittam, Jeffery; Mulholland, Joan (The Electronic Journal of Communication / La Revue Electronic de Communication, 2003)
The design of Internet Relay Chat (IRC) affords for, and itself produces, non-response situations that are not possible in FTF or telephone interaction. These system-occasioned non-responses produce almost isomorphic stimuli to participant non-responses. Situations thus arise in which non-responses are interpersonally accountable despite agentive ambiguity. This study explores four intersections of participant-action and system-occasioned non-responses. An extension to Pomerantz's (1984b) 'pursuing a response' problems/solutions is proposed. The impact of IRC's design on its popularity is discussed in contrast to more recent chat systems. Suggestions are made for active and passive presence and non-response accounting features in future chat systems.
Rintel, E.S., Pittam, J., & Mulholland, J. 2003. Time will tell: Ambiguous non-responses on Internet Relay Chat. The Electronic Journal of Communication, 13, (1). Online version is free and best version (Use Publisher URL)